Figurativização e a estrutura seriada da telenovela - Médola, Ana Sílvia Lopes Davi (2005)
The soap opera (telenovela), and in the same way other fiction texts, have a figurative component which is intrinsically connected to the semionarrative level, because the figurativization is one of the levels through which there is a concretization of the sense. But in the soap opera (telenovela), the procedures of figurativization acquire a wider dimension, because they act not only as the sense of reality effects construction resource, but also forge, by the demarcation of identity and diversity, textual configurations that act as facilitators of the fruition thus reinforcing the identification and the interest of the audience in the plot.